HR Innovations out of Recession - An Appreciative Text and Opinion Analysis - Barman, Arup (Gyan Management Journal, 2012)
We come across the statement elsewhere that ’recession is about the creative Human Resources Management’. The HRM Function is asked to bring new ideas, to change the HRM processes and to develop or change the procedures. And this effort has to be cheap or it has to cut the costs of the organization. The HRM Innovation is easy in times of the business growth, but the recession is not good for big innovative HRM Initiatives. Still, we can distinguish the HR innovation to face the recession in many literatures. The present paper aims to appreciate HR innovations out of recession by applying an appreciative text analysis of existing literature. To achieve the central aim of the study, the authors wants to categories the techniques of HR Innovations and also attempting to find out the fulcrum of innovation in the referred literatures with the support of email survey and thus, the paper appreciates the post crisis HR innovation practices in India.